2017
DOI: 10.7251/bii1701032s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-related quality of life among adult patients with type 2 diabetes mellitus

Abstract: SummaryIntroduction.The aim of the study was to find out the determinants of the quality of life in primary health care patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous literature has confirmed the fact that a lower HbA1c level is associated with better QoL and, as this level increases, QoL deteriorates. 32 Previous literature reported that disease control among diabetic patients was one of the most important determinants of QoL. 33–35 Furthermore, checking glucose levels on a regular basis may be beneficial for glycemic control and may be a preventive factor for QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has confirmed the fact that a lower HbA1c level is associated with better QoL and, as this level increases, QoL deteriorates. 32 Previous literature reported that disease control among diabetic patients was one of the most important determinants of QoL. 33–35 Furthermore, checking glucose levels on a regular basis may be beneficial for glycemic control and may be a preventive factor for QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic neuropathy can also present with symptoms such as paresthesias, numbness, and tingling in the hands and feet, which can lead to a mix-up between vitamin B12 deficiency and diabetic peripheral neuropathy diagnosis [2]. Thus, early discovery of vitamin B12 deficiency could slow the progression of neurological damage, and if misdiagnosed as diabetic neuropathy, this vitamin B12 shortage could lead to permanent neurological impairment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin therapy in diabetes can substantially affect the quality of life positively by reducing symptoms of high blood sugar, or negatively by increasing symptoms of low blood glucose. 8 The aim of the study was to investigate the risk of long-term use of Metformin induces Vitamin-B12 deficiency amongst Type II diabetic patients and evaluate their quality of life. The Objectives stand to determine the levels of Vitamin B12 in diabetic patients concerning control population, to Study the association between vitamin B12 and peripheral neuropathy and lastly assess their quality of life by using WHO-BREF scale.…”
Section: Introductionmentioning
confidence: 99%